Effect of seed coating material and storage containers on Germination and seedling Vigour of soybean (Glycine max L.) (SAARC Journal of Agriculture, 2015)
A laboratory experiment was conducted to evaluate the effect of different seed coating materials and storage containers on germination, seedling vigour and suitability of packaging material for soybean seed. Seed of soybean varietyPS1024 was used for coating purpose with 6 coating treatments viz., T0 (control), T1 (Polymer coating i.e. Polykote @ 3 ml kg-1 of seed diluted with 5 ml of water), T2 (Flowable Thiram i.e. Royal flow 40 SC @ 2.4 ml kg-1 of seed), T3 (T1 + T2), T4 (Vitavax 200 i.e.thiram 37.5 % and carboxyl 37.5% @ 2 g kg-1 of seed and T5(T1+ T4). The coated seeds were stored in two kinds of containers i.e. jute canvas bag, high density poly ethylene (HDPE) non- laminated bag and bimonthly observation on germination and seedling vigour were recorded. After 8th month of storage, germination and vigour index in polythene bag stored seeds were significantly higher than the seed stored in cloth bag. Among seed coating treatments, maximum %germination was recorded in polymer coating @ 3 ml kg-1 followed by vitavax 200 @ 2 g kg-1of seed treatment (T5) which was significantly higher than rest of the coated treatment including untreated control seeds (T0 ). Similarly, maximum seed vigour index was observed in T5 and minimum vigor index was recorded with T0 (untreated control). DOI: http://dx.doi.org/10.3329/sja.v12i2.21913 SAARC J. Agri., 12(2): 16-24 (2014)